Answer:
The complete expression is : (x + 4 )² = (x + 4)(x + 4)
Explanation:
We are given the equation as : (x + ____ )² = _____
Now, this is said to be a trinomial and as the trinomial contains three terms. So, we need to fill the first blank in such a way that when we expand it, we get three terms
Let the first blank be 4
⇒ The given expression reduces to : (x + 4)²
Now, expanding the above equation
⇒ x² + 8x + 16
Now, we need to form the factors of this expression
⇒ x² + 4x + 4x + 16
⇒ x(x + 4) + x(x + 4)
⇒ (x + 4)(x + 4)
Hence, the complete expression is : (x + 4 )² = (x + 4)(x + 4)